2010
DOI: 10.1021/am100541d
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Stability Improvement of P3HT:PCBM-Based Solar Cells by Thermally Evaporated Chromium Oxide (CrOx) Interfacial Layer

Abstract: We report on thermally evaporated chromium oxide (CrO x ) as cathode interfacial layer to improve the efficiency and stability in air for the bulk heterojunction solar cells of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C61 butyric acid methyl ester (PCBM). Devices with CrO x interfacial layers show higher power conversion efficiency (PCE) and stability than those without interfacial layer. Devices with CrO x show improved stability more than 100 times that of devices without interfacial layer or with Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…However, both thin layers are easily destabilized by further device processing. The top P3HT layer, for example, may be perturbed during electrode evaporation 38 and postannealing processes. 39 The bottom 1 nm thick PCBM layer can similarly be perturbed by further annealing steps.…”
Section: Discussionmentioning
confidence: 99%
“…However, both thin layers are easily destabilized by further device processing. The top P3HT layer, for example, may be perturbed during electrode evaporation 38 and postannealing processes. 39 The bottom 1 nm thick PCBM layer can similarly be perturbed by further annealing steps.…”
Section: Discussionmentioning
confidence: 99%
“…[166] M. Wang et al have applied thermally evaporated chromium oxide (CrO x ) between the active layer and the aluminum cathode to enhance stability. [167] Later, M. Wang et al showed a similar effect for copper oxide (CuO x ) as interface layer either alone or together with lithium fluoride. [168] Y. Wang et al found that a 1 nm thick layer of lithium benzoate improved both performance and stability.…”
Section: The Electron Transport Layermentioning
confidence: 95%
“…92 Polymeric TiO x layer synthesized by hydrolysis of titanium (IV) isopropoxide followed by sol-gel reaction exhibited long-term stability even at temperatures as high as 150 C. 93 Similar to the effect of TiOx interlayer, CrO x also showed remarkable improvement in the air-stability of the devices. 94 For P3HT/PCBM solar cells, devices based on CrO x retained 50% of the original PCE after 6 days of exposure to ambient air, in comparison, devices based on LiF interlayer lost about 90% of the original PCE in just 5 h. 94 As a lesson from the organic light-emitting diodes, thin layer of a conjugated polyelectrolyte in the device was found to enhance the efficiency. 95 For example, Seo et al reported enhancement of PCE (5.0 !6.5%) upon introduction of an alcohol soluble ionic conjugated diblock copolymer PF2/6-b-P3TMAHT between the polymer/fullerene active layer and the metal cathode.…”
Section: Modification Of Electrodes: Effect Of Interlayersmentioning
confidence: 99%